Alhagi honey polysaccharides attenuate intestinal injury and immune suppression in cyclophosphamide-induced mice. Issue 15 (15th June 2021) - Cai, Gaofeng; Wu, Yu; Wusiman, Adelijiang; Gu, Pengfei; Mao, Ningning; Xu, Shuwen; Zhu, Tianyu; Feng, Zian; Liu, Zhenguang; Wang, Deyun
Abstract : Cyclophosphamide (CY), extensively used as an anti-cancer agent, could cause diverse side effects, such as immunosuppression and intestinal barrier damage. Abstract : Cyclophosphamide (CY), extensively used as an anti-cancer agent, could cause diverse side effects, such as immunosuppression and intestinal barrier damage. Alhagi honey polysaccharides (AH), polysaccharides isolated from Alhagi honey, are widely known for their anti-tumor and immunomodulatory activities. Herein, AH are evaluated for their ability to protect mice from CY-induced toxicity. The results demonstrated that treatment with AH could prevent the reduction in spleen and thymus indices as well as body weight, and significantly increase the Peyer's patch count in CY-induced mice and the levels of IL-2, IL-6, and TNF-α in serum, suggesting the role of Alhagi honey polysaccharides in alleviating the immunosuppression induced by CY. Moreover, administration of AH significantly increased the SOD activity and the expression level of β-defensin while decreasing the MDA content and DAO activity in CY-treated mice, which suggested a protective effect of AH on the intestinal barrier. Simultaneously, a CY-induced decrease in the ratio of villi length/crypt depth and the number of intraepithelial lymphocytes and goblet cells was reversed by AH treatment, as were the alterations in the expression of ZO-1, mucin-2, E-cadherin and occludin in the intestine and the concentrations of SCFAs in the colon. Furthermore, AH have the ability to regulate the MAPK pathway in CY-mice models to reduce CY-induced toxicity, evidenced by the increased expression of p-ERK and inhibited production of both p-JNK and p-p38. Overall, these results showed that AH could be used as protective agents to mitigate intestinal injury and immune suppression in mice induced by CY.